Incorporation of zirconium in medium-pore aluminophosphate molecular sieves with AFO framework - Chakrabortty, Dhruba; Ganguli, J. N.; Satyanarayana, C. V. V. (Microporous and Mesoporous Materials, 2011)
Zirconium substituted medium pore microporous aluminophosphate molecular sieve ZrAPO-41 was prepared by hydrothermal synthesis under autogenous pressure The formation of the pure phase was confirmed by powder X-ray diffraction (XRD) and scanning electron microscopy (SEM)The thermal behaviour of the material was investigated by carrying out thermogravimetric/differential thermal analysis (TGA/DTA) The zirconium environment was studied by magic-angle spinning nuclear magnetic resonance (MAS NMR) spectroscopy which suggests incorporation of zirconium into the framework UV-Visible diffuse reflectance study also supports the claim The temperature programmed desorption (TPD) of ammonia reveals that the acidity of ZrAPO 41 samples is higher than that of pure AlPO4-41 The catalytic activity of the samples was investigated through phenol hydroxylation reaction The result show hi E her catalytic activity for ZrAPO-41 samples compared to AlPO4-41 (C) 2010 Elsevier Inc All rights reserved
Keywords: AFO; Aluminophosphate; catalysis; Molecular sieve; ZrAPO 41